Dinamika Boikot Produk Pro-Israel pada Akun Instagram @Gerakanbds - Nazhyfa, Alya; M. Nur, Hasan Basri; Meliya Sari , Fitri (Da’watuna: Journal of Communication and Islamic Broadcasting, 2026)
This study examines the dynamics of pro-Israel product boycott campaigns disseminated through the Instagram account @gerakanbds as a form of digital activism within the Indonesian socio-political context. The research focuses on how boycott messages are constructed, communicated, and circulated through visual content and audience interactions on social media. Employing a qualitative descriptive approach with qualitative content analysis, this study analyzes seven purposively selected Instagram posts uploaded between 2024 and 2025 that explicitly promote boycotts against products affiliated with or perceived to support Israel. Data were collected through digital documentation, including screenshots of posts, captions, and audience comments, and analyzed using thematic coding techniques. The findings reveal that the boycott campaign relies heavily on standardized visual infographics featuring brand logos and lists, combined with moral and humanitarian framing to delegitimize targeted products. The communication strategy emphasizes collective responsibility, ethical consumption, and solidarity with Palestine, positioning boycott practices as a form of symbolic resistance and social pressure in the digital sphere. Audience engagement is manifested through likes, comments, and content sharing, indicating participatory involvement in reinforcing boycott narratives. This study concludes that the @gerakanbds account plays a significant role in mobilizing public opinion and shaping digital discourse surrounding pro-Israel product boycotts, demonstrating how social media functions as a key arena for contemporary activism and consumer-based political expression.